Controle e operação em sistemas quânticos fotônicos - Goes, Felipe da Costa (2017)
In this work the concepts of quantum mechanics on a photon device are studied. The variation in its relative phase is obtained through of the variation in the optical path, whtih is controlled through the refraction index of a waveguide. The main objective of the project is to construct the control from the parameters of a quantum system, aiming for the design construction of a control methodology, through subsequent relations of the measure on the phase of the system, in order to control the external parameters responsible for the phase variation.